Estimating heritability of wool shedding in a cross‐bred ewe population. (4th May 2016) - Vargas Jurado, N.; Leymaster, K.A.; Kuehn, L.A.; Lewis, R.M.
Summary: Low wool prices and high production costs in sheep systems have resulted in the introduction of genotypes that shed wool into flocks to reduce shearing costs. Wool shedding occurs naturally in a few breeds and can be incorporated by cross‐breeding. The opportunity to enhance shedding through selection depends on the extent of genetic variability present. Genetic and environmental parameters for wool shedding for ewes from a three‐breed composite population were estimated using Bayesian inference. Data on 2025 cross‐bred ewes, including 3345 wool shedding scores (WS) and 1647 breeding weight (BW) records, were analysed using bivariate and, for WS, univariate animal repeatability models. Breeding weight was included to account for possible selection bias. Breeding weight was moderately heritable and highly repeatable with means of 0.317 and 0.724, respectively. Under both models, WS was found to be moderately heritable and repeatable with means of 0.256 and 0.399, respectively. Based on a cumulative link model and contingency table analysis, age and reproductive activity influenced the extent of WS (p < 0.05). Given that WS is moderately heritable, selective gain in WS can be achieved.